Roman Phrygia : Culture and Society - Thonemann, Peter (Cambridge : Cambridge University Press, 2013)
The bleak steppe and rolling highlands of inner Anatolia were one of the most remote and underdeveloped parts of the Roman empire. Still today, for most historians of the Roman world, ancient Phrygia largely remains terra incognita. Yet thanks to a startling abundance of Greek and Latin inscriptions on stone, the cultural history of the villages and small towns of Roman Phrygia is known to us in vivid and unexpected detail. Few parts of the Mediterranean world offer so rich a body of evidence for rural society in the Roman Imperial and late antique periods, and for the flourishing of ancient Christianity within this landscape. The eleven essays in this book offer new perspectives on the remarkable culture, lifestyles, art and institutions of the Anatolian uplands in antiquity.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).